2018
DOI: 10.1186/s12943-018-0807-z
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic fusion proteins adopt the insulin-like growth factor signaling pathway

Abstract: The insulin-like growth factor-1 receptor (IGF1R) has been identified as a potent anti-apoptotic, pro-survival tyrosine kinase-containing receptor. Overexpression of the IGF1R gene constitutes a typical feature of most human cancers. Consistent with these biological roles, cells expressing high levels of IGF1R are expected not to die, a quintessential feature of cancer cells. Tumor specific chromosomal translocations that disrupt the architecture of transcription factors are a common theme in carcinogenesis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 90 publications
1
17
0
Order By: Relevance
“…The closeness of certain pairs of gene loci in the nucleus has been found to be positively correlated with their probability of translocations . Numerous disease‐specific chromosomal rearrangements have been linked to different tumor types, constituting the foundation for current molecular diagnostics and treatment . The Philadelphia chromosome discovered by Hungerford and Nowell in 1959 has become a canonical example of such rearrangements.…”
Section: Chromosome Translocationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The closeness of certain pairs of gene loci in the nucleus has been found to be positively correlated with their probability of translocations . Numerous disease‐specific chromosomal rearrangements have been linked to different tumor types, constituting the foundation for current molecular diagnostics and treatment . The Philadelphia chromosome discovered by Hungerford and Nowell in 1959 has become a canonical example of such rearrangements.…”
Section: Chromosome Translocationsmentioning
confidence: 99%
“…2,43 Numerous disease-specific chromosomal rearrangements have been linked to different tumor types, constituting the foundation for current molecular diagnostics and treatment. [44][45][46] The Philadelphia chromosome discovered by Hungerford and Nowell in 1959 has become a canonical example of such rearrangements. The mechanism identified almost 15 years later is based on a translocation between chromosome 9 and 22 resulting in BCR/ABL1 fusion gene formation which is responsible for chronic myeloid leukemia, and thus it serves as a target for immunotherapy.…”
Section: Chromosome Translocationsmentioning
confidence: 99%
“…Studies in recent decades have shown that several oncogenic gene fusions interact with insulin-like growth factor (IGF) signaling at different levels [14,15]. IGF signaling is an ancient evolutionary conserved mechanism that regulates critical cellular processes such as cell proliferation and survival [16].…”
Section: Introductionmentioning
confidence: 99%
“…Tumorigenesis in translocation-driven tumors is critically mediated via the IGF-1R signaling pathway [117]. Preclinical models of Ewing sarcomas show an autocrine activation of the IGF-1R-mediated signaling pathway [118], which promotes cell viability and drug escape [119,120].…”
Section: Ewing Sarcomamentioning
confidence: 99%